Bidimensional Diagnostics, Variability, and Trends of Northern Hemisphere Blocking - Chiara Cagnazzo; Antonio Navarra; Paolo Davini; Silvio Gualdi (Journal of Climate, 2012)
AbstractIn this paper, Northern Hemisphere winter blocking is analyzed through the introduction of a set of new bidimensional diagnostics based on geopotential height that provide information about the occurrence, the duration, the intensity, and the wave breaking associated with the blocking. This analysis is performed with different reanalysis datasets in order to evaluate the sensitivity of the index and the diagnostics adopted. In this way, the authors are able to define a new category of blocking placed at low latitudes that is similar to midlatitude blocking in terms of the introduced diagnostics but is unable to divert or block the flow. Furthermore, over the Euro-Atlantic sector it is shown that it is possible to phenomenologically distinguish between high-latitude blocking occurring over Greenland, north of the jet stream and dominated by cyclonic wave breaking, and the traditional midlatitude blocking localized over Europe and driven by anticyclonic wave breaking. These latter events are uniformly present in a band ranging from the Azores up to Scandinavia. Interestingly, a similar distinction cannot be pointed out over the Pacific basin where the blocking activity is dominated by high-latitude blocking occurring over eastern Siberia. Finally, considering the large impact that blocking may have on the Northern Hemisphere, an analysis of the variability and the trend is carried out. This shows a significant increase of Atlantic low-latitude blocking frequency and an eastward displacement of the strongest blocking events over both the Atlantic and Pacific Oceans.